PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA FLIPBOOK DALAM MENINGKATKAN KETRAMPILAN MEMBACA SISWA SD - Cindyanawati, Fera; Ermawati, Diana; Purbasari, Imaniar (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the implementation of the Discovery Learning model assisted by Flipbook media in improving students’ reading skills. The research employed Classroom Action Research (CAR) developed by Kemmis and Taggart, involving 32 third-grade students of SD 1 Kedungdowo as subjects. Data were collected through observation, interviews, and documentation, and analyzed using qualitative data analysis techniques. The results showed that the use of Discovery Learning assisted by Flipbook media effectively improved students’ reading skills. In the first cycle, the mastery percentage reached 64%, which increased to 74% in the second cycle. These findings indicate that the Discovery Learning model combined with Flipbook media is an effective strategy for enhancing reading skills in third-grade students.